Elevated plasma GLP-1 levels and enhanced expression of cardiac GLP-1 receptors as markers of left ventricular systolic dysfunction: a cross-sectional study. Issue 9 (3rd September 2013) - Hattori, Arihiro; Kawamura, Itta; Yamada, Yoshihisa; Kanamori, Hiromitsu; Aoyama, Takuma; Ushikoshi, Hiroaki; Kawasaki, Masanori; Nishigaki, Kazuhiko; Tamemura, Genzou; Minatoguchi, Shinya
Abstract : Objective: We aimed to elucidate usefulness of plasma glucagon-like peptide-1 (GLP-1) levels for the assessment of left ventricular (LV) dysfunction by examining the relationship among plasma GLP-1 levels, expression of cardiac GLP-1 receptors and LV function in patients with impaired and preserved LV function. Design: Prospective study. Setting: Number of participating center: 1, Gifu, Japan. Participants: Number of patients enrolled: 102 patients who underwent elective cardiac catheterisation for coronary artery disease, cardiomyopathy and valvular heart disease, and 6 patients who underwent cardiac biopsy. Results: The plasma GLP-1 level was significantly increased in patients with impaired LV function (5.7±1.9 pmol/L) as compared with those with preserved LV function (2.7±1.6 pmol/L). Plasma GLP-1 and plasma brain natriuretic peptide (BNP) levels were inversely correlated with the LV ejection fraction(EF), respectively. Plasma GLP-1 level positively correlated with plasma BNP level. Multivariate logistic regression analysis revealed that plasma GLP-1 level was an independent determinant of the impaired LV function, whereas plasma BNP level was not. Intensity of immunostaining for GLP-1 receptor protein was significantly enhanced in patients with impaired LV function compared with those with preserved LV function. Conclusions: The plasma GLP-1 level was increased in patients with impaired systolic LV function and inversely correlated with the LVEF. The expressions of GLP-1 receptors were enhanced in hearts with impaired LV function. These may suggest that endogenous GLP-1-GLP-1 receptor system serves as a compensatory mechanism for systolic LV dysfunction. Trial registration: UMIN-CTR, ID=UMIN000009361, registration number: R000011000.